Program Kemitraan Masyarakat Stimulus pada Rumah Singgah dan Rumah Belajar Cinderella Kota Batam - Sri Langgeng Ratnasari; Gandhi Sutjahjo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The Stimulus Community Partnership Program aims to empower women, street children and people with disabilities. Empowering women, especially women detainees at Batam City Baloi Detention Center, single-parent women who are not able to, and empowering street children who are members of the Cinderella Batam Learning Center. This community service stimulus uses the literature study method using qualitative and descriptive analysis, and the andragogy method. Andragogy method is a method that emphasizes and implements Participatory Action Programs from participants through training, discussion, group work, and field demonstrations in all activities. The implementation of this stimulus community partnership program with assistance, empowerment, and training improves the quality of doll making and online marketing. The products in the form of Cinderella dolls are donated to cancer patients, with disabilities starting in Indonesia, ASEAN countries, and several European countries. After the implementation of the Stimulus Community Partnership Program, results were obtained in the form of improving the quality of making Cinderella dolls and increasing the income of the Cinderella Shelter House and Learning House from online marketing.